Boon, Gerard K. Technology transfer in fibres, textil and apparel. Sijthoff & Noordhoff : Alphen aan den Rijn, The Netherlands, 1981. 581 p. - Rattner, Henrique (Estudios Demográficos y Urbanos, 1983)
BOON, GERARD K, Technology transfer in fibres, textil and apparel, Sijthoff & Noordhoff, 1981, Alphen aan den Rijn, The Netherlands.